PERSIAPAN PRA NIKAH REMAJA DENGAN KEJADIAN STUNTING - Johanis Kerangan; Angela A. M. L. Laka; Wahyuny Langelo; Cindi T. M. Oroh (Universitas Sam Ratulangi, 2023)
Backgroud: Stunting is a growth and development disorder experienced by children, as a result of a long-term lack of nutrition. This growth retardation has a negative impact on children's productivity and cognitive abilities. Stunting can occur not only because the mother's nutrition is not fulfilled during pregnancy but starts from the readiness or reproductive health of the woman.. Purpose : The purpose of this research was to look at the factors that cause stunting in toddlers in the Sangihe Archipelago District, North Sulawesi Province.. Result: This study used an analytic observational design with a case control approach. The total sample was 68 parents who had stunted and non-stunted toddlers in the Manente and Tona Health Centers. The results of the analysis using the Chi-Square test and the Fisher Exact Test showed that there was a relationship between adolescent reproductive health, especially tetanus vaccine before marriage (ρ = 0.013) and premarital assistance (ρ = 0.000) with the incidence of stunting in toddlers in Sangihe Islands District. ). Conclusion:There is a relationship between female adolescent reproductive health and the incidence of stunting, it is necessary to carry out further prevention and treatment efforts. As an effort to accelerate the reduction of stunting in toddlers in Sangihe Islands Regency, nurses collaborate with the government to provide education to teenagers and prospective brides about reproductive health, making tetanus vaccine before marriage and pre-marital assistance as one of the conditions that must be met in managing marriage files. Keywords: Pre-Marriage; Teenagers; Stunting